Tlingit home interior, Sitka, Alaska, 1887 - Partridge, William H.
Interior of large single room, wooden step down onto main floor. Two men sit by central fire pit, women in blankets sit in rear by step. Tables, chairs, household items & beds line walls of room. Caption on mount: Alaska, U.S. Sitka. Partridge Publisher. 69 Morrison St., Portland, Or. PH Coll 322.43